2011
DOI: 10.1111/j.1460-2695.2011.01553.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a residual stress field on fracture initiation in RPV steel

Abstract: A B S T R A C T Whether flaws in structures containing residual (secondary) stresses will extend under particular operational (primary) loads depends on the extent to which the residual stress field affects: (a) the nature and distribution of initiators; (b) the combined (primary + secondary) stresses and strains experienced by potential initiators. This paper compares fractographic data from specimens loaded by only a primary stress with data from specimens also containing a tensile residual stress field. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Curve fitting parameters in Eq. (7) by regress of the test data for steel plates and butt weld are also indicated by Fig. 8; the comparison of the results between the base material and the butt weld is made as well.…”
Section: Variation Law Of the D M Values For Steel Plates And Butt Wementioning
confidence: 97%
See 1 more Smart Citation
“…Curve fitting parameters in Eq. (7) by regress of the test data for steel plates and butt weld are also indicated by Fig. 8; the comparison of the results between the base material and the butt weld is made as well.…”
Section: Variation Law Of the D M Values For Steel Plates And Butt Wementioning
confidence: 97%
“…23,24 Therefore, in this study, the average d m values obtained by tests were regressed according to Eq. (7) in the form of Boltzmann function, where d 1 , d 2 , T t and T r are curve fitting parameters; T represents the temperature variable; d(T) is the critical value of CTOD at temperature T; d 1 and d 2 are the CTOD critical values of the lower and upper shelf, respectively; T t is the ductile to brittle transition temperature and T r is the temperature range of transition region.…”
Section: Variation Law Of the D M Values For Steel Plates And Butt Wementioning
confidence: 99%
“…Thijs et al [6] studied the influence of different scanning speeds with the alternating and the unidirectional scan vector on the microstructure of the Ti-6Al-4V alloy processed by SLM. Ortner et al [7] found that residual stress could improve the fracture toughness of steel. A traditional heat treatment process is also a method of the surface strengthening treatment of SLM specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of WRS would be harmful to safety and intensity of pressure vessel [1][2][3][4]. One of the most important methods to evaluate if the welding structure is safe is calculating stress intensity factor (K) of crack.…”
Section: Introductionmentioning
confidence: 99%